"Dear Amy": Seeking support on YouTube. Issue 1 (22nd October 2020) - Salib, Gabrielle; Gorichanaz, Tim; Agosto, Denise E.
Abstract: Among many other video genres, YouTube is a hub for "how‐to" videos, including advice on how to work through difficult life circumstances. For this pilot study, we investigated a sample of comments in response to two Amy Poehler's Smart Girls' "Ask Me Anything" videos. Geared toward adolescents and emerging adults, "Ask Me Anything" videos respond to viewer questions on social, personal, and professional topics, such as coping with embarrassment, worries about school exams, relationship power dynamics, and general life stress. In our analysis, we identify emerging trends in the language of viewers' response comments and investigate (a) how viewers are responding to the videos, and (b) what such responses could mean for the design of social computing systems and their use for social and emotional support. We find indications of users' emotional support seeking, evidence of adult audience members' seeking to answer younger responders' questions posted in response to the videos, and the use of epistolary forms to express perceived emotional connections with the video host. In future work, we will seek to understand what elements of the videos are invoking such personal connections and explore designs of social computing systems to better support personal connection and intergenerational support online.